DISEQUILIBRIUM PARTIAL MELTING EXPERIMENTS ON THE LEEDEY L6 CHONDRITE: TEXTURAL CONTROLS ON MELTING PROCESSES - Feldstein S.N.; Jones R.H.; Papike J.J. (My University, 2001)
A series of experiments were designed to investigate the textural and compositional changes that take place during disequilibrium partial melting of chondritic material. Chips of the L6 chondrite, Leedey, were heated at 1200 °C and log ƒO2 = IW-1 for durations of 1 h to 21 days. We observed a progression of kinetically-controlled textural changes in melt and restite minerals and changes in the liquidus mineralogy in response to factors such as volatile loss. During the course of the experiments, both olivine and orthopyroxene recrystallized at different times. Rare relic chondrules could still be identified after 21 days. The silicate melts that form are very heterogeneous, in terms of both major and trace element chemistry, reflecting heterogeneity of the localized mineral assemblage, particularly with respect to phosphates and clinopyroxene. Metal-sulfide melts formed in short-duration runs are also heterogeneous. The experimental data are relevant to aspects of the genesis of primitive achondrites such as the acapulcoites. The observed textures are consistent with a model for acapulcoite petrogenesis in which silicate melting was limited to only a few volume percent of the chondritic source rock. The experiments are also relevant to the behavior of chondritic material that has been partially melted in an impact environment.
Keywords: chondrite